OLD AND NEW CONTRADICTIONS OF CAPITALISM: GEOGRAPHICAL PERSPECTIVES - Franco Salvatori (Bollettino della Società Geografica Italiana)
The modern capitalistic system coincides – except for some sporadic, few cases – with the World System. As for other main political events, when capitalism triumphs that is the moment of its decline. Reasoning on the contradictions of capitalism, much more can be said from the geographical perspective in addition to what Harvey wrote in his last work. A key role, indeed, can be played by the geographical levels of the capitalistic processes, about the consequences on the new phases of poverty, on the uses of technology in a territorial sense on the use of the environmental heritage. This contribution proposes some reflections on the Harvey’s book, focusing the attention on the geographical dimension of the capitalism’s processes, on its consequences on territories and on the relations between human beings and the environments.